Utilising social network research in the qualitative exploration of gamblers' social relationships. (April 2018) - Dobbie, Fiona; Reith, Gerda; McConville, Susan
Social Network Analysis (SNA) is often criticised for being too quantitative in focus and network scientists have commented on a lack of engagement from qualitative researchers. This article will contribute to these debates by critically reflecting on a qualitative study of gambling where social network research methods were adapted and applied to narrative interviews. Egocentric sociograms (maps of participant social networks, using a name generation question and concentric circles) were created for 23 participants. These sociograms were used as an interactive tool, with the addition of coloured dots, to stimulate discussion and so generate rich narrative and visual data on the impacts of gambling behaviour on participants' wider social networks. This approach represents an extension to existing SNA methods that has not previously been utilised.